Penerapan asas praduga tak bersalah pada harta kekayaan yang patut diduga untuk pendanaan terorisme - Pranowo, Prayogo (Jurnal Cakrawala Hukum, 2020)
Money laundering is a form of further criminal acts committed to eliminate traces of wealth obtained from crime / criminal offenses, in Law No. 8 of 2010 concerning Money Laundering in Article 2 paragraph 2 it is explained that an asset, if used for terrorism activities, whether it is suspected or known, it will be equated with money laundering, there is a conflict in the sentence "should be suspected" and "equated as the result of a criminal act" wherein in the presumption of innocence a person cannot be found guilty before there is a decision permanent legal force judges, normative legal research methodology with a statute approach, and conceptual approach, while the formulation of the issues to be discussed in this study are: The legal basis for the presumption of innocence in the crime of money laundering, handling of assets belonging to terrorism in Article 2 of the Law on Money Laundering and Related Regulations, and the purpose of this research are: to find out and analyze the relationship between the presumption of innocence against limiting money laundering in terms of using wealth against terrorism financing, to find out and analyzing the application of the principle of presumption of innocence to the eradication of money laundering in terms of using wealth against terrorism financing. How to cite item:Â Pranowo, P. (2020). Penerapan asas praduga tak bersalah pada harta kekayaan yang patut diduga untuk pendanaan terorisme.Â Jurnal Cakrawala Hukum, 11(1), 91-101. doi:https://doi.org/10.26905/idjch.v11i1.3539